Causes and Consequences of the Syndrome of Excessive Bacterial Growth in the Small Intestine - Vladimir Leonidovich, Martynov (Journal of Human and Animal Intestines, 2020)
Currently, there is a paradoxical situation where the dominant opinion in medicine recognizes the harmfulness of dysfunction of such barrier structures as the cardia, pylorus, sphincter of Oddi, heart valves, valves of the veins of the lower extremities, etc., but ignores the failure of the ileocecal obturator (bauginium damper) or its absence as a possible cause of the pathology of the digestive system, as well as various extraintestinal diseases 1. But also I.I. Grekov (1952) expressed his position 2, which remained relevant: “Despite a number of works devoted to the proximal part of the large intestines, the pathology of this department is still insufficiently explained because the role of the Bauginium damper was completely ignored in these works.
Keywords: pathology; digestive system; bacterial growth